2008
DOI: 10.2337/db07-1499
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular High-Mobility Group Box 1 Acts as an Innate Immune Mediator to Enhance Autoimmune Progression and Diabetes Onset in NOD Mice

Abstract: OBJECTIVE— The implication of innate immunity in type 1 diabetes development has long been proposed. High-mobility group box 1 (HMGB1), an evolutionarily conserved chromosomal protein, was recently recognized to be a potent innate inflammatory mediator when released extracellularly. We sought to test the hypothesis that HMGB1 acts as an innate immune mediator implicated in type 1 diabetes pathogenesis. RESEARCH DESIGN AND METHODS— Eight- and 12-week-old NOD mice were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
76
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 43 publications
7
76
0
1
Order By: Relevance
“…HMGB1 antibodies (Abs) were produced by immunizing New Zealand white rabbits with rHMGB1 and Abs with neutralizing activities were tested as reported. 23 Affinity-purified antiCD8a (clone 53-6.7) and IL-17A-neutralizing mAb (clone TC11-18H10.1) and control rat IgG were purchased from Biolegend (San Diego, CA, USA). FITC-labeled anti-CD4 (clone GK1.5), FITC-labeled anti-CD8a (53-6.7), PE-labeled anti-IFN-g, PE-labeled anti-IL-17 (clone TC11-18H10), and purified rat anti-mouse CD4 (clone RM4-5) were purchased from BD Pharmingen (San Jose, CA, USA).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…HMGB1 antibodies (Abs) were produced by immunizing New Zealand white rabbits with rHMGB1 and Abs with neutralizing activities were tested as reported. 23 Affinity-purified antiCD8a (clone 53-6.7) and IL-17A-neutralizing mAb (clone TC11-18H10.1) and control rat IgG were purchased from Biolegend (San Diego, CA, USA). FITC-labeled anti-CD4 (clone GK1.5), FITC-labeled anti-CD8a (53-6.7), PE-labeled anti-IFN-g, PE-labeled anti-IL-17 (clone TC11-18H10), and purified rat anti-mouse CD4 (clone RM4-5) were purchased from BD Pharmingen (San Jose, CA, USA).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…Defects in apoptotic β cell clearance have been considered as an important cause of type 1 diabetes [20][21][22][23][24], although the underlying mechanisms remain elusive. To illustrate the importance of HMGB1 in this process, we confirmed that HMGB1 could be passive released by apoptotic β cells, not only by necrotic cells [6]. Defective clearance of apoptotic β cells may thereby results in the accumulation of extracellular HMGB1.…”
mentioning
confidence: 53%
“…It has been suggested that HMGB1 is involved in the pathogenesis of multiple autoimmune diseases including Systemic Lupus Erythematosus (SLE), Rheumatoid Arthritis (RA), and Experimental Allergic Encephalomyelitis (EAE) [4,5]. We recently demonstrated that HMGB1 is also implicated in the development of type 1 diabetes via activating innate immune response [5,6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wie bei anderen Autoimmunerkrankungen auch, kann HMGB1 dendritische zellen aktivieren und die Immunantwort gegen k ö rpereigene Betazellen lenken. Die Gabe von Anti-HMGB1-Antik ö rper konnten auch hier die Inzidenz reduzieren und den Krankheitsverlauf mildern [81,82] .…”
Section: Relevanz Von Hmgb1 Und Rage F ü R Die Pathophysiologie Nichtunclassified